Age-specific Peri-ictal Electro-clinical Features of Generalized Tonic Clonic Seizures and Potential Risk of Sudden Unexpected Death in Epilepsy (SUDEP) - Freitas, Joel (2013)
Generalized tonic-clonic seizures (GTCS) are the commonest seizure type associated with Sudden Unexplained Death in Epilepsy (SUDEP). This study examines semiological and electroencephalographic differences (EEG) in the GTCS of adults as compared to children. The rationale lies in epidemiological observations that have noted a ten-fold higher incidence of SUDEP in adults. We analyzed video-EEG data of 105 GTCS in 61 consecutive patients (12 children, 23 seizures and 49 adults, 82 seizures) recruited from the Epilepsy Monitoring Unit. Semiological, EEG and 3-channel EKG features were studied. Peri-ictal seizure phase durations were analyzed including tonic, clonic, total seizure, post-ictal EEG suppression (PGES) and recovery phases. Heart rate variability (HRV) measures including RMSSD (root mean square successive difference of R-R intervals), SDNN (standard deviation of NN intervals) and SDSD (standard deviation of differences) were analyzed (including low frequency/high frequency power ratios) during pre-ictal baseline, ictal and post-ictal phases. Generalized estimating equations (GEE) were used to find associations between electro-clinical features. Separate subgroup analyses were carried out on adult and pediatric age groups as well as medication groups (no anti-epileptic medication cessation versus unchanged or reduced medication) during admission. Major differences were seen in adult and pediatric seizures with total seizure duration, tonic phase, PGES and recovery phases being significantly shorter in children (p<0.01). GEE analysis using tonic phase duration as the dependent variable, found age to correlate significantly (p<0.001) and this remained significant during subgroup analysis (adults and children) such that each 0.12 second increase in tonic phase duration correlated with a 1 second increase in PGES duration. PGES durations were on average 28 seconds shorter in children. With cessation of medication, total seizure duration was significantly increased by a mean value of 8 seconds in children and 11 seconds in adults (p<0.05). Tonic phase duration also significantly increased with medication cessation and although PGES durations increased, this was not significant. RMSSD was negatively correlated with PGES duration (longer PGES durations were associated with decreased vagally mediated heart rate variability; p<0.05) but not with tonic phase duration. This study clearly points out identifiable electro-clinical differences between adult and pediatric GTCS that may be relevant in explaining lower SUDEP risk in children. The findings suggest that some prolonged seizure phases and prolonged PGES duration may be electro-clinical markers of SUDEP risk and merit further study.